Validitas Modul Interaktif Pembelajaran IPA untuk Meningkatkan Kemampuan Berpikir Kreatif - Heny Mawarni; Arif Sholahuddin; Badruzsaufari Badruzsaufari (Program of Biology Education, Universitas Lambung Mangkurat, 2022)
The development of creativity is included in one of the focuses of the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. One way to develop students' creativity is to develop creative thinking skills. This study aims to describe the validity of interactive modules in science learning to improve students' creative thinking skills in junior high schools. This study uses a 4D research and development model design. Data were collected using validity instruments and legibility test questionnaires, then analyzed descriptively. The research subjects consisted of 5 expert validators and 2 students. The results showed (1) the validity of the interactive science learning module met the very valid category with an average result of 86.07. (2) the readability test of the interactive science learning module met the